Rasa Concept in the Aesthetics of Classical Indian Music - Tamošaitytė, Daiva (Acta Orientalia Vilnensia, 2000)
The article discusses the rasa concept in the aesthetics of classical Indian music. There is given an explication of rasa theory in some main scripts of Indian scholars, raga and ragini as basic forms of classical Indian music, their deification and visualisation in Indian philosophy and poetry. The author observes rasa doctrine according to Bharata’s Nāyaśāstra, Abhinavagupta’s The Abhinavabhāratī, Śargadeva’s Sañgītaratnākara, Bhaa Nāyaka and gives nowadays view of contemporary authors, such as Sri Aurobindo, A. Daniélou, S. Ch. Dey, V. Raghavan and O. C. Gangoly. The theory of rasa was developed on the basis of Sanskrit treatises by eminent theoreticians (alamkārikās). From about XIII century the rasa theory becomes very important aesthetic doctrine in an emerging independent musical theory. Still until now it is an integral part of the whole Indian aesthetic–philosophical thought and must be regarded as an universal principle in order to concieve the Indian classical music on its highest level – the transcendental pure beauty, that transforms emotions and manifests as sat–cit–ānanda, or Self–aware Delight of transcendent Existence.